Expression and functional pharmacology of the bradykinin B1 receptor in the normal and inflamed human gallbladder. Issue 5 (8th January 2008) - Andre, E; Gazzieri, D; Bardella, E; Ferreira, J; Mori, M A; Saul, V V; Bader, M; Calixto, J B; De Giorgio, R; Corinaldesi, R; Geppetti, P; Trevisani, M
Abstract : Background and aims: It has recently been described that bradykinin B2 receptors are expressed in the human gallbladder and that their activation induces a powerful contraction, especially in acute cholecystitis tissues. Here the role of the B1 receptor in the contractility of control and inflamed human gallbladder was investigated. Methods: Strips of human gallbladder from either acute gallstone cholecystitis or elective gastro-entero-pancreatic surgery (control) were assessed in vitro and processed for reverse transcription-PCR analysis. Cumulative concentration–response curves with the selective B1 receptor agonist, Lys-Des-Arg 9 -bradykinin, cholecystokinin and carbachol were performed in control and cholecystitis specimens. Results: Lys-Des-Arg 9 -bradykinin concentration-dependently contracted strips of control gallbladders and its motor effect was higher in inflamed gallbladders. Lys-Des-Arg 9 -bradykinin-induced contraction was not altered by pretreatment with the selective bradykinin B2 receptor antagonist, HOE140 (1 μM), the NK1 (SR140333), NK2 (SR48968) and NK3 (SR142801) tachykinin receptor antagonists (all 1 μM), the muscarinic acetylcholine receptor antagonist, atropine (1 μM), and the cyclo-oxygenase inhibitor, indomethacin (5 μM). In contrast, the Lys-Des-Arg 9 -bradykinin-induced motor response was significantly reduced by the selective B1 receptor antagonist, R-715. Finally, quantitative real-time PCR analysis indicated that B1 receptor mRNA levels were significantly higher in cholecystitis smooth muscle specimens, when compared with that observed in control tissues. Conclusions: Bradykinin B1 receptor has an important role as a spasmogen of human gallbladder, and selective antagonists of the B1 receptor may represent a valid therapeutic option to control pain in patients with acute cholecystitis.